Letter: Covid‐19—re‐initiating clinical services for chronic gastrointestinal diseases. How and when? Authors' reply - Prentice, Ralley E. (Aliment Pharmacol Ther, 2020)
LINKED CONTENT This article is linked to Al‐Ani et al and Britton et al papers. To view these articles, visit https://doi.org/10.1111/apt.15779 and https://doi.org/10.1111/apt.16061